Uncovering the Spatial Patterning of Crimes: A Criminal Movement Model (CriMM). (March 2014) - Reid, Andrew A.; Frank, Richard; Iwanski, Natalia; Dabbaghian, Vahid; Brantingham, Patricia
Objectives: The main objective of this study was to see if the characteristics of offenders' crimes exhibit spatial patterning in crime neutral areas by examining the relationship between simulated travel routes of offenders along the physical road network and the actual locations of their crimes in the same geographic space. Method: This study introduced a Criminal Movement model (CriMM) that simulates travel patterns of known offenders. Using offenders' home locations, locations of major attractors (e.g., shopping centers), and variations of Dijkstra's shortest path algorithm we modeled the routes that offenders are likely to take when traveling from their home to an attractor. We then compare the locations of offenders' crimes to these paths and analyze their proximity characteristics. This process was carried out using data on 7, 807 property offenders from five municipalities in the Greater Vancouver Regional District (GVRD) in British Columbia, Canada. Results: The results show that a great proportion of crimes tend to be located geographically proximal to the simulated travel paths with a distance decay pattern characterizing the distribution of distance measures. Conclusion : These results lend support to Crime Pattern Theory and the idea that there is an underlying pattern to crimes in crime neutral areas.